Solid malignant retroperitoneal masses in children in a low resource setting: epidemiology, clinicopathologic characteristics, treatment, prognostic and quality of life after surgery; a cross-sectional analytic study - Landry W. Tchuenkam; Axel S. Nwaha Makon; Angele H. Pondy Ongotsoyi; Jean E. Bayiha; Bernadette Ngo Nonga (Elsevier, 2023)
Background: Solid retroperitoneal masses in children are frequent in pediatrics' oncology. The diagnosis must be prompt and precise in order to initiate appropriate treatment options. These treatment options takes into account; the histological type, staging, associated comorbidities and the child's tolerance to mainly chemotherapy as well radiotherapy which is often employed. This preliminary study is part of a better understanding of retroperitoneal solid cancer in black children, more specifically in Cameroon and in particular on the data concerning the epidemiology, the diagnostic process, the therapeutic options, the results of the treatment and related difficulties to children's care in daily practice. Objectives: To determine the clinical, therapeutic and prognostic profile of children treated for solid retroperitoneal masses and also assess the health-related quality of life the cancer survivors in a tertiary hospital in Cameroon. Materials and method: We carried out a descriptive cohort study at the Mother and Child Center of the Chantal Biya Foundation (MCC-CBF), in Cameroon. The study concerned children followed in the pediatric oncology center from 2007 to 2019 who presented with a solid retroperitoneal tumor and received complete management. The health-related quality of life was assessed using the ''Pediatric Quality of life Scale'' (PedsQL). The data was analyzed with IBM_SPSS software version 20.0. The analysis of survival data was carried out according to the Kaplan Meier's method. The alpha risk was set at a threshold of 5% Results: A total of 84 children with solid retroperitoneal masses were included in our study with 74 cases of nephroblastoma and 10 cases of neuroblastoma. The median age of the children at diagnosis was 3.9 years. The main clinical manifestations found were; abdominal distension, abdominal pain, abdominal mass, weight loss, anorexia and prolonged fever. Out of the 74 cases of nephroblastoma, 73% of the cases were localized tumors while on the other hand 90% of the neuroblastomas were metastasized. The course of treatment was neoadjuvant chemotherapy followed by surgery and adjuvant chemotherapy in 80 children. Four children with tumor rupture underwent primary surgery without neoadjuvant chemotherapy. The 2-year survival rate was 71.6% for nephroblastoma and 30% for neuroblastoma, respectively. The health-related quality of life of the surviving children was rated as satisfactory. Conclusion: Solid retroperitoneal masses in child are a group of curable cancer in our context. Postoperative morbidity is lower, with almost zero mortality. The health-related quality of life of children surviving after surgery is good